Correlations Between the Autolytic Changes and Postmortem Interval in Refrigerated Cadavers - Cocariu Ela Andra; Mageriu V.; Stăniceanu Florica; Bastian Alexandra; Socoliuc C.; Zurac Sabina (Sciendo, 2016)
Introduction. In forensic pathology the autolytic process has been observed and documented in order to determine the postmortem interval as accurately as possible. The observation and experiments have been carried out on cadavers exposed to environmental conditions - heat, humidity, air currents, soil, water.